On the Validation of a Specific Development Process for Scientific Software using the Inspection Technique DOI - 10.5752/P.2316-9451.2015v3n2p3 - Gomes, Jether Oliveira; Moita, Gray Farias (Abakós, 2015)
The increasing demand for software has generated greater need for software development processes. However, although the literature does not present processes for the development of scientific software, in previous studies, a Specific Development Process for Scientific Software (SDPSS) was proposed. SDPSS was conceived based on Humphrey’s Methodology, which defines that the execution of eight steps is necessary for the acquisition of a process. Having in mind that the first six steps have already been carried out, the current study considers the accomplishment of the seventh and eighth steps of the Methodology, which are the validation of the initial process and its later improvement. It is important to highlight the significance of these steps because a process must be tested and validated to ensure its efficiency. Hence, first, a webapp to automate and model the SDPSS was developed to aid in its implementation. Subsequently, SDPSS was applied in real environments of scientific software development to obtain results that were analyzed through a validation technique by inspection, known as VProcInsp. Despite some inconsistencies, it was concluded that SDPSS can really contribute to the development of academic scientific software.